From space to movement: the walk as an intellectual dynamic in Diderot's La Promenade du sceptique (Itinera, 2021)
Diderot's Promenade du sceptique has sometimes been criticised for a somewhat systematic use of allegory, associated with a tripartite division of space summarising and tracing, between the thorns of devotion, the flowers of worldly life, and the chestnut trees of philosophy, the three paths of life available to men. The work's device is nevertheless much more complex and elaborate, and is affected by a diffuse scepticism from within. Open rather than closed, the space and the places of the walk in La Promenade du sceptique are misleadingly the support of an analogical understanding of the world. The writing of the walk becomes a metaphor for the intellectual dynamic that doubts and searches. Movement in its temporal dimension, as a concrete experience, challenges the conception of a geometric space, mocks deism as well as idealism, and opens the way to the experimental method and the materialist hypothesis.
Keywords: walking, Diderot, garden, 18th century French literature, philosophical dialogue